Activation of BDNF-TrkB signaling pathway-regulated brain inflammation in pentylenetetrazole-induced seizures in zebrafish. Issue 83 (December 2018) - Jin, Meng; Sheng, Wenlong; Han, Liwen; He, Qiuxia; Ji, Xiuna; Liu, Kechun
Abstract: Seizures are sustained neuronal hyperexcitability in brain that result in loss of consciousness and injury. Understanding how the brain responds to seizures is critical to help developing new therapeutic strategies for epilepsy, a neurological disorder characterized by recurrent and unprovoked seizures. However, the mechanisms underlying seizure-dependent alterations of biological properties are poorly understood. In this study, we analyzed gene expression profiles of the zebrafish heads that were undergoing seizures and identified 1776 differentially expressed genes. Gene-regulatory network analysis revealed that BDNF-TrkB signaling pathway positively regulated brain inflammation in zebrafish during seizures. Using K252a, a TrkB inhibitor to block BDNF-TrkB signaling pathway, attenuated pentylenetetrazole (PTZ)-induced seizures, which also confirmed BDNF-TrkB mediated inflammatory responses including regulation of il1β and nfκb, and neutrophil and macrophage infiltration of brain. Our results have provided novel insights into seizure-induced brain inflammation in zebrafish and anti-inflammatory related therapy for epilepsy. Highlights: Gene expression profiling of seizures identifies 1776 differentially expressed genes. Regulatory analysis suggests BDNF-TrkB regulated brain inflammation during seizures. Pretreatment of K252a to block BDNF-TrkB inhibits the PTZ-induced seizure responses. Blocking BDNF-TrkB inhibits seizure-induced increase of inflammatory-related genes. Activation of BDNF-TrkB during seizures triggers leukocyte infiltration into the head.